2001
DOI: 10.1577/1548-8675(2001)021<0884:dotlfa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Littoral Fish Assemblage in Spirit Lake, Iowa, and Implications for Prey Availability for Piscivores

Abstract: We assessed the dynamics of the littoral fish assemblage in Spirit Lake, Iowa, and examined potential consequences of these dynamics for availability of prey fish for piscivores. Using beach seines, we quantified the annual, seasonal, and spatial variation in density and biomass of the entire assemblage and of component species over a 4-year period. Potential prey fish availability was inferred from the biomass of the cumulative total fish length groups and sizes of fish eaten by piscivores. Total fish density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Pelham (2000) sampled the offshore zone at night from May to September 1998 using a semiballoon otter trawl (Hayes et al 1996) with a 7.9-m headrope, a 38-mm-mesh body, and a 6-mm-mesh cod end. Trawling was done during the same weeks as littoral zone beach seining (Pierce et al 2001b), allowing a direct comparison of relative densities in the littoral zone versus offshore. Pooled over the entire 1998 study period, mean offshore densities of black crappie, largemouth bass, northern pike, and smallmouth bass were less than 1 fish/ha and 95% confidence intervals (CIs) all included zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelham (2000) sampled the offshore zone at night from May to September 1998 using a semiballoon otter trawl (Hayes et al 1996) with a 7.9-m headrope, a 38-mm-mesh body, and a 6-mm-mesh cod end. Trawling was done during the same weeks as littoral zone beach seining (Pierce et al 2001b), allowing a direct comparison of relative densities in the littoral zone versus offshore. Pooled over the entire 1998 study period, mean offshore densities of black crappie, largemouth bass, northern pike, and smallmouth bass were less than 1 fish/ha and 95% confidence intervals (CIs) all included zero.…”
Section: Discussionmentioning
confidence: 99%
“…Angling pressure is high, and walleye Sander vitreus (formerly Stizostedion vitreum) and yellow perch Perca flavescens are among the most sought-after species. The predominant piscivorous fish species are yellow perch, walleye, black crappie Pomoxis nigromaculatus, largemouth bass Micropterus salmoides, smallmouth bass Micropterus dolomieu, and northern pike Esox lucius, which together account for 99% of the density and 97% of the biomass of all piscivorous fish in Spirit Lake (Pierce et al 2001b). Despite over a century of regular stocking and length and bag limits, walleye growth rate and size structure in Spirit Lake have declined from historical levels, resulting in reduced harvest and angler satisfaction (Rose 1955;Jennings 1970;Larscheid 1994).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Most small fishes in the Yangtze lakes spawn between April and August, and more larval and juvenile individuals of several species in our study were observed in spring or summer. The availability of small fish as prey for piscivorous predator can be effected by prey size structure and predator's size-selective feeding (Pierce et al 2001). Therefore, we suggested that the favorable seasons for stocking juvenile piscivorous fishes should be late spring or early summer when the small fishes with suitable size are most abundant in the lakes.…”
Section: Implications For Lake Fishery Managementmentioning
confidence: 99%
“…This idea has never been extended to entire fish communities, but may be applicable in systems like Lake Texoma, where littoral-zone communities are less complex and structured by physical variables that vary little from year to year (e.g., site exposure or water clarity). Furthermore, many littoral-zone fishes serve as prey for many larger-bodied sport fishes; thus, consistency or lack thereof in communities may have major implications for resident piscivores (mostly sport fishes) or the stocking success of fingerling piscivores (Pierce et al 2001).…”
Section: Concordance Of Larval Juvenile and Adult Fishesmentioning
confidence: 99%